Physical activity profile of women in the urban municipality of Catarman, Northern Samar - Lelix, Ida M.
The study explored the knowledge, perception, and practices on physical activity among the adult women in the urban barangays of Catarman. The specific objectives of the study included description of the activity level of women in the occupational, non-occupational, and transportation domains of physical activity; their knowledge level and perceptions of the benefits of physical activity in the prevention of cardiovascular diseases, and guidelines of physical activity and exercise; description of their perceived barriers to physical activity and exercise; determination of the prevalence of selected risk factors of cardiovascular diseases including hypertension, and obesity (BMI, WHR); and the relationship between physical activity, hypertension, and obesity (BMI, WHR); and recommendation of a health promotion program on physical activity based on the findings of the study. The study utilized a descriptive cross-sectional design with two methods of data gathering: the first, through the use of structured questionnaire, designed for interview and second through an in-depth discussion of issues by a focus group discussion (FGD). The respondents were determined through a two-stage cluster sampling design where five out of the 22 urban barangays were randomly selected. Respondents were located by the number of households in each of the identified barangays. He total respondents were 528 women.
To answer the objectives of the study, the main tool utilized was the standardized Global Physical Activity Questionnaire (GPAQ) of the World Health Organization from STEPwise Approach to Surveillance of NCD Risk Factors (2001) which was translated to Waray and back translated to English. The other instrument utilized was the respondent's profile and the knowledge test. The tool utilized for the focus group discussion was developed by the investigator with the help of a content expert who analyzed and scrutinized the questions. Based on the findings, more than half (55.3%) of the respondents were between 18 and 35 years of age; almost half (40.2%) of them were college level graduates; majority (86.2%) of the respondents had a monthly income below 10,802 pesos. Majority (96.6%) did not smoke. The overall physical activity profile showed 74.8% moderately active women, compared to the inactive (20.8%) and highly active (4.4%). To determine the knowledge level in terms of health benefits and guidelines of physical activity and exercise, five questions mostly from the knowledge of benefits out of the nine items were found to be significant as compared to a=0.05 level of significance. Knowledge and education were associated, p=0.003403, but education and level of physical activity did not show association, p=0.19781. Focus group discussion was done in six groups of women to determine perceptions on the barriers of physical activity and exercise. Most respondents said that house hold chores and taking care of children, lack of social support, laziness, and lack of time as some of the hindrances to physical activity. Menopausal women seldom did structured physical activity. However, both the single and menopausal women knowledge on the importance of warm-up exercise as a good guideline.
Thesis (M.A. Nursing)--University of the Philippines Manila.
Keywords: Physical fitness for women; Women -- Philippines